KINERJA GURU SENI BUDAYA MENDORONG KEWIRAUSAHAAN MANDIRI DI SEKOLAH MENENGAH KEJURUAN (SMK) SE KOTA MALANG - Muhammad ‘Afaf Hasyimy; Yuyun Nur Astuti; Dewi Jasmine; Robby Hidajat (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2020)
This article examines the work of art and culture teachers applying entrepreneurship lessons in Vocational High Schools (SMK) throughout Malang, East Java. Entrepreneurship encourages student entrepreneurship from working in the industrial sector and government institutions. Receiving students to move industries that continue to improve The purpose of this study is to examine teacher performance Encouraging students to become entrepreneurs. This research method is descriptive quantitative. Data collection techniques through a questionnaire with Google Form on 11 art and culture teachers who are members of the Subject Teachers Association (MGMP) throughout Malang. Vocational Middle School (SMK) in Malang City is a school that is demanded from the implementation of entrepreneurship so that students have a great opportunity to utilize it as industrial technical personnel. The results showed more male teachers than female teachers, 54.5% male teachers, 45.5% educational background, as motivating students to produce applied art 81.8%. While male teachers are able to encourage students to practice as sellers of school work in markets close to the school. Key Words: Vocational High School, Entrepreneurship, Cultural Arts Teacher, Applied Arts